1996
DOI: 10.1136/bjsm.30.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low dose oral contraceptives on exercise performance.

Abstract: Objective-to examine the effect of cycle phase or a low dose oral conraceptive on exercise performance in young women. Methods-As controls, 15 men were tested twice by a maximal treadmill test (Vo2 max) and by an endurance run 14 d apart to determine performance variability from causes other than hormonal fluctuations. Ten women ages 18-30 were then tested for VO2 max and endurance in the same way in both the follicular and the luteal phase (random order, ovulation assessed by sonography). They were then rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 10 publications
4
30
2
Order By: Relevance
“…And, finally, the duration of OC use may play a role. Longer than 1 mo of OC use appears to be necessary to induce physiological changes because a study examining 1-3 wk of monophasic OCs found no significant effect on V O 2 peak (2).…”
Section: Discussionmentioning
confidence: 99%
“…And, finally, the duration of OC use may play a role. Longer than 1 mo of OC use appears to be necessary to induce physiological changes because a study examining 1-3 wk of monophasic OCs found no significant effect on V O 2 peak (2).…”
Section: Discussionmentioning
confidence: 99%
“…Combined oral contraceptive use may reduce VO 2max although this is less apparent in trained athletes [58][59][60][61][62][63][64][65] .…”
Section: Oxygen Uptakementioning
confidence: 99%
“…Many studies have shown that OC use results in a significant reduction in maximal oxygen uptake (VO 2max ) in non-athletic women after 2-6 months use 53,[58][59][60][61][62] which is reversed when OC use is terminated 58,60 . is may be due to a reduced activation of the sympathetic nervous system in ovarian suppressed women 63 or a reduction in mitochondrial citrate 58 .…”
Section: Is Oxygen Uptake Affected By Hormonal Contraceptive Use?mentioning
confidence: 99%
See 2 more Smart Citations